Statistical Modelling of Recent Changes in Extreme Rainfall in Taiwan - Lan-Fen Chu; Michael McAleer; Szu-Hua Wang (Tinbergen Institute, 2012)
This paper has two primary purposes. First, we fit the annual maximum daily rainfall data for 6 rainfall stations, both with stationary and non-stationary generalized extreme value (GEV) distributions for the periods 1911-2010 and 1960-2010 in Taiwan, and detect the changes between the two phases for extreme rainfall. The non-stationary model means that the location parameter in the GEV distribution is a linear function of time to detect temporal trends in maximum rainfall. Second, we compute the future behavior of stationary models for the return levels of 10, 20, 50 and 100-years based on the period 1960-2010. In addition, the 95% confidence intervals of the return levels are provided. This is the first investigation to use generalized extreme value distributions to model extreme rainfall in Taiwan.
urn:NBN:nl:ui:15-1765/38224
Keywords: Q54; Q51; Q57; 330; Generalized extreme value; Extreme rainfall; Return level; Statistical modelling; Wetter; Sturm; Statistische Verteilung; Taiwan